2021
DOI: 10.1126/sciadv.abd2827
|View full text |Cite
|
Sign up to set email alerts
|

Autism-linked gene FoxP1 selectively regulates the cultural transmission of learned vocalizations

Abstract: Autism spectrum disorders (ASDs) are characterized by impaired learning of social skills and language. Memories of how parents and other social models behave are used to guide behavioral learning. How ASD-linked genes affect the intertwined aspects of observational learning and behavioral imitation is not known. Here, we examine how disrupted expression of the ASD gene FOXP1, which causes severe impairments in speech and language learning, affects the cultural transmission of birdsong between adult and juvenil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 63 publications
0
27
0
Order By: Relevance
“…For example, one study reported that lesions within NCM did not significantly interfere with the accurate sensorimotor development of song (22,80). In addition, a number of experiments have suggested that tutoring-dependent plasticity within the sensorimotor nucleus HVC (used as a proper name) is critical for the sensory learning of song (81)(82)(83)(84)(85). In this respect, it is possible that NE infusions into NCM allow for greater tutoring-dependent plasticity within sensorimotor circuitry.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study reported that lesions within NCM did not significantly interfere with the accurate sensorimotor development of song (22,80). In addition, a number of experiments have suggested that tutoring-dependent plasticity within the sensorimotor nucleus HVC (used as a proper name) is critical for the sensory learning of song (81)(82)(83)(84)(85). In this respect, it is possible that NE infusions into NCM allow for greater tutoring-dependent plasticity within sensorimotor circuitry.…”
Section: Discussionmentioning
confidence: 99%
“…RELN (reelin) [133][134][135]. FOXP1 (forkhead box protein P1) [136][137][138][139]. SYNGAP1 (synaptic Ras GTPase-activating protein 1) [140,141].…”
Section: Genes and Geneticsmentioning
confidence: 99%
“…Moreover, recent genomic research has identified potential genetic substrates for the evolution and regulation of vocal communication ( Warren et al, 2010 ). Furthermore, expression of the ASD gene FOXP1 is reported to cause severe impairment in speech/language learning and affect the cultural transmission of bird songs between adult and juvenile zebra finches ( Garcia-Oscos et al, 2021 ).…”
Section: Common Animals Used In Asd Studymentioning
confidence: 99%